The impact of childhood epilepsy on quality of life: a qualitative investigation using focus group methods to obtain children's perspectives on living with epilepsy. - Moffat, C; Dorris, L; Connor, L; Espie, C (2009)
As children's perceptions of their quality of life are unique, it is essential to elicit their concerns directly rather than from proxy informants. This study therefore aimed to investigate the impact of childhood epilepsy on quality of life directly from the child's perspective. Focus group techniques and qualitative analysis were utilized. Twenty-two children between 7 years 4 months and 12 years 6 months of age (11 females, 11 males) were stratified by age (7-8, 9-10, 11-12 years) into five focus groups. Data were transcribed and analyzed using grounded theory techniques to generate themes and categories. Themes were presented using the children's language. Two major themes were identified, "things to do with growing up" and "things to do with epilepsy," with five and four subthemes, respectively. No significant age-related differences were found. A conceptual model illustrates these findings, and comparisons are made to previous research with adolescents using similar methodology.